The Organization of Neglect: Limited Liability Companies and Housing Disinvestment. Issue 1 (February 2019) - Travis, Adam
Sociological accounts of urban disinvestment processes rarely assess how landlords' variable investment strategies may be facilitated or constrained by the legal environment. Nor do they typically examine how such factors might, in turn, affect housing conditions for city dwellers. Over the past two decades, the advent and diffusion of the limited liability company (LLC) has reshaped the legal landscape of rental ownership. Increasingly, rental properties are owned by business organizations that limit investor liability, rather than by individual landlords who own property in their own names. An analysis of administrative records and survey data from Milwaukee, Wisconsin, demonstrates that signs of housing disinvestment increase when properties transition from individual to LLC ownership. This increase is not explained by selection on property characteristics or by divergent pre-transfer trends. Results affirm that real estate investors are responsive to changes in the legal environment and that the protective structure of the LLC facilitates housing disinvestment in Milwaukee. Elaborating the role of real estate investors can deepen accounts of neighborhood change processes and help explain variation in local housing conditions. Ultimately, public policies that enable business operators to circumscribe or reallocate risk may generate unintended costs for consumers and the public.